2006
DOI: 10.1016/j.neuroimage.2005.10.054
|View full text |Cite
|
Sign up to set email alerts
|

Statistical parametric mapping of brain morphology: Sensitivity is dramatically increased by using brain-extracted images as inputs

Abstract: A major attraction of voxel-based morphometry (VBM) is that it allows researchers to explore large datasets with minimal human intervention. However, the validity and sensitivity of the Statistical Parametric Mapping (SPM2) approach to VBM is the subject of considerable debate. We visually inspected the SPM2 gray matter segmentations for 101 research participants and found a gross inclusion of non-brain tissue surrounding the entire brain as gray matter in five subjects, and focal areas bordering the brain in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 18 publications
4
45
0
Order By: Relevance
“…These AS errors were seen in 25% (14/56) of all subjects. Similar errors have been reported in the analysis of T 1 -weighted MRI using SPM2 and were eliminated by the removal of signals from non-brain tissues (Fein et al 2006). On the other hand, 3D-SSP is relatively insulated from the influence of such tracer distributions because it uses a number of landmarks for AS.…”
Section: Discussionsupporting
confidence: 63%
“…These AS errors were seen in 25% (14/56) of all subjects. Similar errors have been reported in the analysis of T 1 -weighted MRI using SPM2 and were eliminated by the removal of signals from non-brain tissues (Fein et al 2006). On the other hand, 3D-SSP is relatively insulated from the influence of such tracer distributions because it uses a number of landmarks for AS.…”
Section: Discussionsupporting
confidence: 63%
“…SPM2, in its standard form implements voxel-based morphometry using T1-weighted brain images that include the scalp, skull and meninges as inputs, and incorporates a morphological clean-up step to remove 'non-brain' tissue. In a recent manuscript (Fein et al, 2006), we found that: 1) SPM2 does a poor job removing the non-brain tissue, 2) poor alignment of individual brains with the brain in the MNI template, resulting in an incorrect delineation of cortical gray matter, and 3) that this incorrect delineation of cortical gray matter dramatically increases the error term in the SPM2 analyses, reducing the sensitivity of standard SPM2 to detect experimental effects. We modified the SPM2 processing pipeline to accept skull-stripped inputs and demonstrated that the modification reduced the error term by about one third, with concomitant increases in the sensitivity to detect experimental effects.…”
Section: Introductionmentioning
confidence: 97%
“…We examined these brain regions, using T1-weighted MRIs, in the 101 participants from our previous study using voxel-based morphometry (VBM). VBM was performed using a modification we developed (Fein et al, 2006) of Baron's procedure, (Baron et al, 2001), in which we use skullstripped images as input. We also restricted the analysis to a ROI consisting of the amygdala and VMPFC as defined by the Talairach Daemon resource.…”
mentioning
confidence: 99%
“…In the past decade, voxel-based morphometry (VBM) (Ashburner and Friston, 2000) has been extensively applied to statistically reveal regions with significant structural discrepancy between image groups (Good et al, 2001a, b;Beyer and Krishnan, 2002;Brenneis et al, 2003;Karas et al, 2003). Recent studies indicated that accurate brain extraction can improve the validity of VBM results because of better tissue segmentation and brain registration (Fein et al, 2006;Acosta-Cabronero et al, 2008).…”
Section: Introductionmentioning
confidence: 99%